2010
DOI: 10.4166/kjg.2010.56.5.299
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Conventional 4 L Polyethylene Glycol and Combination of 2 L Polyethylene Glycol and Sodium Phosphate Solution as Colonoscopy Preparation

Abstract: PEG 2 L with NaP 90 mL method seems to be more effective bowel preparation than PEG 4 L method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Whether different bowel preparation drugs show different effectiveness remains controversial. Previous reports have suggested that bowel preparation is associated with not only drugs, but also drug compliance and fiber diet education [35,36]. Our study showed that there was a sex difference in bowel preparation status using bowel preparation drugs.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Whether different bowel preparation drugs show different effectiveness remains controversial. Previous reports have suggested that bowel preparation is associated with not only drugs, but also drug compliance and fiber diet education [35,36]. Our study showed that there was a sex difference in bowel preparation status using bowel preparation drugs.…”
Section: Discussionsupporting
confidence: 55%
“…We analyzed various guidelines for adequate bowel preparation and found that females showed bet- ter bowel preparation results. It is known that bowel preparation is influenced by various factors [11][12][13]35,36]. Our study showed that sex factor could influence bowel preparation based on a large cohort database.…”
Section: Discussionmentioning
confidence: 58%
“…Another study published in Korea investigated the efficacy and safety of 2 L PEG using two doses of 45 mL NaP compared with 4 L PEG in a nonrandom manner 16. However, our present study is the first large prospective randomized trial comparing 2 L PEG with a single dose of 45 mL NaP and 4 L PEG for bowel cleansing before colonoscopy.…”
Section: Discussionmentioning
confidence: 89%
“…13,2830 To date, however, few studies have investigated combinations of 2 different bowel-cleansing agents. 22,31 Our hypothesis was that the combination of 2 different regimens at half dosage could augment the strength of each regimen while also reducing side effects. In this prospective, randomized, single-blind, phase II study, we evaluated the efficacy, tolerability, and side effects of 4 different combination regimens: PMC-PEG-DP, PMC-PEG-SD, PMC-NaP-DP, and PMC-NaP-SD.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Combination regimens of different preparations at reduced volumes could benefit patients by enhancing the quality of bowel cleansing and improving compliance. However, there has been limited evidence regarding the utility of combined regimens and their clinical use for bowel cleansing.…”
Section: Introductionmentioning
confidence: 99%